A formative evaluation of the parent infant home visiting programme - Percival, Sheridan-Lee (Organisational Psychology, 2022)
Background The Parent-Infant Home Visiting Programme (PIVHP) is a home-based parenting programme targeted at new and expectant mothers, characterised as vulnerable. Participants are recruited from low-income communities situated on the Cape Flats, in Cape Town, South Africa. The programme consists of antenatal and postnatal sessions, facilitated by trained Parent Infant Attachment Counsellors (PIACs) recruited from target communities. There are two programme cycles per year: one from January to June, and a second one from July to December. The overarching goal of PIHVP is to contribute towards the prevention of child abuse, abandonment and neglect; and to promote positive infant growth and development. The programme has to date not been guided by an explicit theory of change (TOC). There was no Monitoring and Evaluation (M&E) system in place, at the time of the evaluation, either. The programme engages in extensive data collection for administrative purposes. This data, however, is not captured nor analysed systematically to monitor progress or measure impact. This formative evaluation aims to capitalise on the existing data. Evaluation Focus This evaluation focused on the first 2019 programme cycle. The main objective of this evaluation was to determine the extent to which the PIHVP had been implemented with fidelity. As such, a process evaluation was conducted to address the following evaluation questions: 1. Did the PIHVP beneficiaries recruited for the first 2019 programme cycle meet the eligibility criteria specified by programme? 2. What proportion of participants completed and dropped out of the PIHVP during the first programme cycle of 2019? What are the reasons provided for programme dropout? questions: 3. To what extent did the PIHVP meet its targeted number of participants? What are the reasons for over/under coverage? 4. Did the participants receive the home-visiting sessions at the duration and frequency prescribed by the programme model? 5. Did PIACs complete and conduct all programme activities, developmental screenings and demonstrations as intended? 6. How did participants perceive PIACs in terms of the support they provided and their preparation level, knowledge, and reliability? 7. To what extent do PIACs implement the skills acquired through their training into their sessions? 8. Are the participants satisfied with the service they received? What are the strengths and limitations they identified? 9. To what extent did participants engage with the PIACs (around the content) during home-visit sessions? Methodology The evaluator first extracted and refined the programme's TOC through structured consultations with the programme manager. The plausibility of the PIHVP's programme theory was then assessed through an extensive literature review. The evaluator then proceeded with the process evaluation. A mixed methods approach was used, as combination of both primary and secondary data sources, and quantitative and qualitative data analysis were used to systematically answer the evaluation questions.